Public Policy and the Refusal to Enforce Foreign Arbitral Awards: A Comparative Analysis of France, Singapore, and Vietnam - Nam, Phan Hoai (Indonesian Journal of International Law, 2025)
The multilateral frameworks governing the recognition and enforcement of arbitral awards, such as the 1958 New York Convention, along with the domestic laws of most states, are generally designed to promote the efficient enforcement of foreign arbitral awards. However, practical experience reveals inconsistencies in its application. While many states adhere to international principles, some - despite being signatories to the Convention - have exploited the broad concept of public policy to unjustifiably refuse enforcement within their jurisdictions. Conversely, other states have adopted a more restrictive approach, limiting the public policy exception to ensure predictability in enforcement. This article focuses on the use of the public policy exception in France and Singapore, where courts have developed relatively clear frameworks. By analyzing these jurisdictions, the article identifies lessons that could enhance Vietnam’s legal framework, particularly in aligning domestic regulations with international standards and limiting the scope of the public policy exception to prevent misuse. The article begins by introducing the topic and outlining the research objectives. It then provides a comprehensive examination of the laws and regulations of both France and Singapore regarding the recognition and enforcement of foreign arbitral awards, focusing on their respective approaches to public policy in arbitration. Finally, Section IV analyzes Vietnam’s current legal framework, offering insights and recommendations drawn from the experiences of France and Singapore to enhance Vietnam’s approach to international arbitration. The article proposes reform measures to align Vietnam’s enforcement framework with global arbitration norms to bolster legal certainty for foreign investors and promote Vietnam as an arbitration-friendly jurisdiction.